The Application of Small Molecules to the Control of Typical Species Associated With Oral Infectious Diseases - Yang, Sirui; Lyu, Xiaoying; Zhang, Jin; Shui, Yusen; Yang, Ran; Xu, Xin (Frontiers in Cellular and Infection Microbiology, 2022)
Oral microbial dysbiosis is the major causative factor for common oral infectious diseases including dental caries and periodontal diseases. Interventions that can lessen the virulence of dysbiotic oral microbiota and reconstitute microbial ecology have drawn increasing attention in the development of novel therapeutics for oral diseases. Antimicrobial small molecules are a series of natural or synthetic bioactive compounds that have shown good inhibitory effect on oral microbiota associated with oral infectious diseases. Novel small molecules, which can either selectively inhibit keystone microbes that drive dysbiotic shift of oral microbiota or inhibit the key virulence of the microbial community without necessarily killing the microbes, are promising for the ecological management of oral diseases. Here we discussed the research progress in the development of antimicrobial small molecules and delivery systems, the mode of action and underlying mechanisms, as well as the potential applications of these compounds in the treatment of oral infectious diseases, with a particular focus on their ecological impact on microbial virulence and ecology, aiming to promote the clinical translation of small molecules to the better management of these diseases.